Global trends and collaborations in bortezomib-induced neurotoxicity research: a bibliometric analysis (2002–2024) - Wang, Pin; Liu, Jiaqi; Cheng, Lingling; Gu, Weiying; Tang, Yunlong; Shao, Yu (Frontiers in Pharmacology, 2025)
ObjectivesHematological malignancies pose significant health challenges, with bortezomib emerging as a key therapeutic agent. However, its use is complicated by neurotoxicity, a side effect that urgently requires mitigation strategies. This study aims to provide a comprehensive bibliometric analysis to map the intellectual structure, historical trends, and emerging research fronts in the field of bortezomib-induced neurotoxicity.MethodsWe conducted a systematic search in the Web of Science Core Collection, capturing literature from 2002 to 2024. Articles written in English were selected for analysis. Bibliometric analysis was performed using VOSviewer, CiteSpace, and R 4.3.3 to visualize collaborations, keyword co-occurrences, and bibliographic coupling.ResultsThe overview of this study reveals a rich tapestry of academic engagement encompassing 745 publications. The USA and China were the most productive countries, with Harvard University and the Dana-Farber Cancer Institute leading in institutional contributions. The New England Journal of Medicine stood out as the most influential journal. Prominent authors like Richardson Paul G. showcased the highest impact, with central research themes focusing on therapeutic approaches and peripheral neuropathy.ConclusionThis bibliometric analysis provides a detailed overview of the research landscape in bortezomib-induced neurotoxicity, identifying the USA and China as leading contributors and highlighting the central focus on therapeutic strategies and peripheral neuropathy management. These findings emphasize the need for global collaboration to develop effective mitigation strategies for neurotoxicity and improve patient outcomes. Insights from this study can guide future research efforts and inform clinical practices in managing bortezomib-related side effects.